The influences of critical incidents and lifecycle dynamics on innovation implementation constructs in SMEs: a longitudinal study. (1st January 2010) - McAdam, Rodney; Mitchell, Neil
Innovation implementation in SMEs involves complex longitudinal dynamics which are driven by market and technological change. From this perspective, innovation implementation is seen as consisting of a number of constructs rather than being restricted to a meta level concept. Moreover, attempts at innovation implementation in SMEs are likely to be influenced by the dynamic effects of critical incidents or crisis points in small firms. The aim of this study is to explore the effects of critical incidents on innovation implementation constructs within a regional cluster of SMEs over a two-year period. The research methodology involves the longitudinal study of a regional cluster of 13 SMEs in relation to innovation implementation constructs at firm level. Participant observation and critical action learning methodologies were used over a two-year period of study. The findings show that some of the SMEs were able to develop innovation implementation across a number of constructs and use critical incidents as catalysts for developing more radical innovation, which was dependant upon their lifecycle stage.